Saccharomyces boulardii modulates oxidative stress and renin angiotensin system attenuating diabetes-induced liver injury in mice - Barssotti, Leticia; Abreu, Isabel C. M. E.; Brandão, Ana Beatriz P.; Albuquerque, Raquel C. M. F.; Ferreira, Fabiana G.; Salgado, Miguel A. C. [UNESP]; Dias, Danielle D. S.; De Angelis, Kátia; Yokota, Rodrigo; Casarini, Dulce E.; Souza, Lívia B.; Taddei, Carla R.; et al. (Springer Nature, 2021)
Type 1 diabetes (T1DM) is a chronic disease characterized by hyperglycemia due to a deficiency in endogenous insulin production, resulting from pancreatic beta cell death. Persistent hyperglycemia leads to enhanced oxidative stress and liver injury. Several studies have evaluated the anti-diabetic and protective effects of probiotic strains in animal models. In the present study, we investigated, through histopathological and biochemical analyses, the effects of eight weeks of administration of Saccharomyces boulardii (S. boulardii) yeast on the liver of streptozotocin (STZ) induced diabetic C57BL/6 mice. Our results demonstrated that S. boulardii attenuates hepatocytes hydropic degeneration and hepatic vessels congestion in STZ-induced diabetic mice. The treatment attenuated the oxidative stress in diabetic mice leading to a reduction of carbonylated protein concentration and increased activity of antioxidant enzymes superoxide dismutase and glutathione peroxidase, compared to untreated diabetic animals. The results also show the beneficial influence of S. boulardii in regulating the hepatic concentration of renin angiotensin system (RAS) peptides. Therefore, our results demonstrated that S. boulardii administration to STZ-induced diabetic mice reduces oxidative stress and normalizes the concentration of RAS peptides, supporting the hypothesis that this yeast may have a role as a potential adjunctive therapy to attenuate diabetes-induced liver injury.